Sibling Position and Marriage Timing in the Netherlands, 1840–1922: A Comparison across Social Classes, Local Contexts, and Time. (April 2014) - Suanet, Bianca; Bras, Hilde
Research on the effects of sibling position on marriage timing has produced ambivalent findings, suggesting that birth order effects were contingent on social, local, and historical contexts. Based on a large database of marriage certificates from five Dutch provinces between 1840 and 1922, we examine the influence of birth order on marriage timing. Our main conclusion is that sibling position became less important for marriage timing during the nineteenth century. This trend can be considered part of the transition from the West-European marriage pattern to a marriage pattern characterized by more universal marriage in which personal preferences became more significant.